Analisis impak pertumbuhan ekonomi ke atas kualiti hidup penduduk di Malaysia - Ishak Yussof,; Mustaffa Omar, (Penerbit ukm, 2008)

(untitled)
Economists have long debated over the impact of economic growth on people’s living standards and their social well being. Many believe that people’s social well being will not be necessarily guaranteed by the increase in economic growth per se or when the growth failed to have a trickled down effect. In fact, in a situation of uncontrolled economic growth, the existence of several negative externalities such as high inflation rate, environmental issues and depletion of resources may have long run effects on people’s social well being. This article aims at analyzing the impact of economic growth on the quality of life in Malaysia. Multiple regression analysis is carried out on all eleven components of the national quality of life data. The analysis is divided into two phases of national development plans, i.e. the second period of New Economic Policy (NEP, 1980-1990) and the period of National Development Policy (NDP, 1991-2000). During the second period of NEP (1980-1990), the impact of economic development is obvious on income and distribution; public safety; social participation and family life components. As for the NDP (1991-2000) period, the impact of economic growth is more discernible on components such as transportation and communication, environment, education and family life